2007
DOI: 10.1897/06-377r3.1
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic organismal toxicity, cytotoxicity, genotoxicity, and feeding response of pacific oyster (Crassostrea gigas) to lindane (γ‐HCH) exposure under experimental conditions

Abstract: This study evaluated organismal toxicity, cytotoxicity, and genotoxicity and the filtration rate in response to different concentrations of subchronic lindane (gamma-hexachlorocyclohexane [gamma-HCH]), exposure (12 d) in adult Pacific oysters Crassostrea gigas. Oysters were exposed in vivo in laboratory aquaria to 10 different concentrations (0.0-10.0 mg/L) of gamma-HCH. The median lethal concentration (LC50) after 12 d was calculated as 2.22 mg/L. Cytotoxic effects were observed in hemocytes, where the mean c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 43 publications
2
14
0
1
Order By: Relevance
“…These results were in agreement with previous studies that reduced NRR was detected in mussels and clams following exposure to contaminants such as metals, organic xenobiotics and antibiotic drugs (Lowe and Moore, 1979;Dailianis et al, 2003;Nigro et al, 2006;Rank et al, 2007;Aguirre-Martinez et al, 2013). DNA damage can lead to reproductive impairment, abnormal development and lethal mutations, which has been used as a general stress biomarker to indicate the genotoxic risk (Anguiano et al, 2007;Barranger et al, 2014;Vazquez-Boucard et al, 2014). The present study clearly demonstrated that oysters from XZ and MP were suffered from significant DNA damage.…”
Section: Discussionsupporting
confidence: 93%
“…These results were in agreement with previous studies that reduced NRR was detected in mussels and clams following exposure to contaminants such as metals, organic xenobiotics and antibiotic drugs (Lowe and Moore, 1979;Dailianis et al, 2003;Nigro et al, 2006;Rank et al, 2007;Aguirre-Martinez et al, 2013). DNA damage can lead to reproductive impairment, abnormal development and lethal mutations, which has been used as a general stress biomarker to indicate the genotoxic risk (Anguiano et al, 2007;Barranger et al, 2014;Vazquez-Boucard et al, 2014). The present study clearly demonstrated that oysters from XZ and MP were suffered from significant DNA damage.…”
Section: Discussionsupporting
confidence: 93%
“…Triforine, a fungicide, induced decreased hemocyte viability in the eastern oyster, Crassostrea virginica (Alvarez & Friedl, 1992). Cytotoxic effects were also observed in adult Pacific cupped oyster, C. gigas, hemocytes: the mean cell viability was significantly decreased at 1.0 mg L -1 of lindane (gamma-hexachlorocyclohexane) after 12 day exposure period (Anguiano et al, 2006). Alteration in cell viability was also reported in the blue mussel, Mytilus edulis, exposed to 0.1 mg L -1 azamethiphos, an organophosphate pesticide (Cantry et al, 2007).…”
Section: Immunotoxicity In Marine Bivalves and Susceptibilty To Infecmentioning
confidence: 91%
“…The induced aneuploidy observed appeared to be transmitted to the next generation as offspring exhibited significantly higher aneuploidy levels when their parents had been exposed to diuron (Bouilly et al, 2007). Genotoxicity induced by lindane at 0.7 mg L -1 was also demonstrated in Pacific oyster, Crassostrea gigas, hemocytes after a 12 day contamination period (Anguiano et al, 2006). Wessel et al (2007) investigatied embryotoxic and genotoxic effects of the organochlorine pesticide, endosulfan, on Crassostrea gigas embryos.…”
Section: Genotoxicity In Marine Bivalvesmentioning
confidence: 96%
See 2 more Smart Citations